The potential economic benefits of insect-based feed in Uganda - Abro, Zewdu; Macharia, Ibrahim; Mulungu, Kelvin; Subramanian, Sevgan; Tanga, Chrysantus Mbi; Kassie, Menale (Frontiers in Insect Science, 2022)
Black soldier fly farming is gaining traction globally as a strategy for recycling organic waste into high-quality proteins and fat for feed and organic fertilizer for crop production. The support of governments in East Africa to integrate insect meal in livestock feed has opened opportunities for commercializing insect products. Understanding the potential value of Black soldier fly larvae meal (BSFLM) is paramount to inform policies and practices to promote insect farming and insect-based feed for livestock production. This paper uses the economic surplus method to generate evidence on the potential socioeconomic impact of replacing conventional soybean and fish meal protein sources with insect-based feed (IBF), BSFLM, in Uganda. Results indicate that the substitution of IBF for existing protein sources will generate net economic benefits of USD 0.73 billion in 20 years (0.037 billion per year). The benefit-cost ratio is estimated at 28:1, and the internal rate of return is 138%, indicating that the insect-based animal feed industry is a profitable investment. Even in the worst-case scenario, when the replacement rate of IBF and its economic benefits are reduced by half, the benefit-cost ratio remains high (8:1). The estimated economic benefit can lift about 4.53 million people above the poverty line in the country. It can also create about 1,252─563,302 new jobs per annum, depending on the substitution rate of conventional protein feeds with IBF (0.1%─45%). Uganda has the potential to produce from about 3,244 tons to 1.5 million tons of IBF. Similarly, using the same replacement rates, the country can produce about 695─312,678 tons of NPK fertilizer from biowaste recycling. About 0.09-41 million tons of biowaste could be recycled, depending on the replacement rate of conventional feed sources with IBF. Our results justify that investing in the insect feed value chain can contribute to Uganda’s economic, social, and environmental sustainability.